2021
DOI: 10.3390/educsci11090537
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Psychomotor Skills in a Virtual Environment: An Educational Case Study

Abstract: In March 2020, most physical therapy schools across the globe transitioned to online learning in response to the COVID-19 pandemic. This change posed unique challenges not only because it required adapting to new technology in a short period but, more importantly, it involved developing ways to teach hands-on psychomotor and clinical skills virtually while maintaining the quality of instruction. In response to the rapid transition, the physical therapy program at MGH Institute of Health Professions (IHP)design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…When looking at part 1 of the survey, CIs reported that all students in the virtual learning group had acceptable overall clinic readiness, which indicates the efficacy of virtual learning as perceived by CIs. As indicated by Plummer et al, 9 recording and rerecording of skills requires extra practice that may not occur outside of the traditional F2F simulation class time. This could contribute to the overall perceived clinic readiness noted by the CIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at part 1 of the survey, CIs reported that all students in the virtual learning group had acceptable overall clinic readiness, which indicates the efficacy of virtual learning as perceived by CIs. As indicated by Plummer et al, 9 recording and rerecording of skills requires extra practice that may not occur outside of the traditional F2F simulation class time. This could contribute to the overall perceived clinic readiness noted by the CIs.…”
Section: Discussionmentioning
confidence: 99%
“…Students reported that recording and rerecording videos provided extra practice time and stated they received adequate feedback to effectively perform the skills being taught. 9 It is important to note that there is very little literature on the comparison of F2F instruction with purely online courses, especially considering the kinesthetic, hands-on nature of physical therapy coursework. The lack of literature on this topic may be attributed to the small number of DPT programs providing this type of learning model.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The rapid switch to online learning posed substantial challenges to HPE, including physical therapy, as face-to-face training and hands-on skill development are essential curricular components. In addition, this abrupt change in didactic delivery required HPE programs to consider how to convert the traditional in-person content, which relies heavily on psychomotor skill development, to a virtual model (Plummer et al , 2021b). In some cases, HPE programs had to rearrange curricular content to keep students safe and on track for graduation (Plummer et al , 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Importance of feedback is further supported by Plummer et al, 17 who investigated the use of virtual instruction to teach psychomotor skills to DPT students. By developing a virtual model with instructor feedback, role-playing, peer feedback, and 1:1 coaching sessions, the students attested that the volume and variety of feedback was beneficial to the performance and acquisition of psychomotor and affective skills.…”
mentioning
confidence: 97%
“…Instructor feedback was reported as the most beneficial, though 86% of students agreed that viewing peer videos positively affected their learning by providing the opportunity to reflect on their own performance. 17 Simulation has provided useful benefits to clinical education and student confidence regardless of the type of patient, physical environment, and clinical setting. 2,8,12,25,26 Although the use of F2F simulation-based learning has proven valuable, there continues to be minimal research assessing the effects of virtual simulation on student confidence and their perception of readiness for clinical practice.…”
mentioning
confidence: 99%